Tinjauan Hukum Islam : Pemikiran Imam Abu Hanifah tentang Transaksi Salam - Tasyqi Masyumatul Aulia; Salsa Bila Rahmawati; Firda Kharisma; Lina Marlina (Journal of Islamic Economics and Finance, 2025)
This research aims to analyze Imam Abu Hanifah's thoughts on salam transactions from an Islamic legal perspective. A salam transaction is a form of sale recognized in Sharia, where payment is made in advance, while the goods are delivered at a later date. This research uses a literature review method with a descriptive analysis approach, examining primary and secondary sources related to Imam Abu Hanifah's thoughts on salam. The results of the research show that Imam Abu Hanifah paid special attention to the valid conditions of salam transactions, with the aim of protecting the rights of both parties and preventing disputes. His thoughts emphasize the importance of clear specifications of goods, delivery time, and price, as well as the prohibition of practices that contain elements of gharar (uncertainty).